Manufacturing as driver of economic growth - Rocha, Igor Lopes (PSL Quarterly Review, 2018)
This study combines different theoretical strands on development regarding the importance of the manufacturing industry for economic growth. Through a confluence of the Keynesian-Kaldorian, structuralist and neo-Schumpeterian frameworks, the paper argues that the manufacturing industry presents some special properties, which are not found in other sectors. The first section describes Anglo-Saxon structuralism, focused on structural change dynamics, and the Latin American structuralist view of underdevelopment, according to which economic development results from technical progress induced or enabled by capital accumulation. The second section examines the Kaldorian approach to growth, understood as “laws”, where Kaldor explains the differences in international growth rates recovering important elements in the contemporaneous debate. The third section investigates the neo-Schumpeterian route to development, exploring relations between innovation, economic dynamics and catching-up in a sectoral specific approach. JEL Code: B10, E12, O1, O14